Revisiting the sermon, carrot and stick theory – En komparativ fallstudie över implementering av styrmedel för plastbärkassar utifrån EU-direktiv i Sverige, Storbritannien och Frankrike - Persson,Anna (2018)
The consumption of plastic bags is a global problem that leads to increased concentration of plastic in the world oceans. In 2014, annual consumption of plastic carrier bags amounted to around 100 billion in the EU, which corresponds to an average of about 200 bags per person per year, of which many plastic bags are used only once and/or end up as waste in nature. This thesis is a comparative case study of the implementations of the European Parliament and Council Directive 2015/720 to reduce the consumption of plastic carrier bags undertaken in Sweden, United Kingdom (UK) and France. The purpose of this paper is to explain how the same political issues are governed by different policy tools in three different countries. Based on the theoretical assumption that policy instruments can be grouped into three categories, ranging from least compelling; voluntary (sermon), to economical means (carrot), to most compelling; regulatory (stick), this thesis is analysing policy documents, preparatory works and policy investigations to seek to explain why countries choose to address the same political issue using different policy tools. Based on earlier studies, experts suggest that the economical instrument (carrot), for an example a plastic bag levy, is the most effective policy instrument for governments to reduce plastic carrier bags consumption, a strategy implemented in the UK. In Sweden and France other alternatives of policy instruments have been implemented; obligation to inform customers (sermon) in Sweden, respectively a ban (stick) in France. Therefore it is of interest to compare these three countries. The findings of this study recognise that tradition appears to be the decisive contextual factor in countries’ choice of policy instrument. There is a strong connection to the nation’s history and preferences that plays a decisive role in the choice of instrument. he study also finds that there are important research gaps in the implementation of policy instruments, especially in terms of exploring which aspects, such as contextual factors, may account for the final choices of policy tools.
Keywords: policy instruments; implementation; plastic carrier bags; governance; environmental policy